Geophysical insights into Tattapani Thermal Spring Azad Kashmir Pakistan: unravelling subsurface geology and geothermal potential - Rashid, Mehboob ur (Journal of Himalayan Earth Sciences, 2025)
Pakistan faces a growing energy demand, and thermal springs represent a potentially significant renewable energy source. This naturally heated thermal water can be harnessed for power generation, space heating, and greenhouses, offering a renewable and sustainable alternative to fossil fuels. Pakistan possesses significant, yet underdeveloped, thermal potential, and exploring and harnessing these resources could yield substantial environmental and economic benefits. The Tattapani thermal spring in Kotli, Azad Kashmir, is investigated for its geothermal energy potential due to its probable high temperatures, favorable geological conditions, and accessibility. The study aims to identify the subsurface geological structure, map the lithology, estimate the depth of the thermal spring reservoir, and infer the migration patterns of the thermal water. The resistivity profile of the Tattapani thermal spring unveiled five distinct layers exhibiting varying resistivity values. The uppermost layer, characterized by a high resistivity zone (> 500Ωm), corresponds to the dolomitic rock of the Abbottabad Formation. The second layer delineates lithological units of Murree sandstone, displaying resistivity values between >200Ωm and ≤500Ωm, indicative of potential meteoric freshwater. The third layer, marked by a resistivity range of >50Ωm to ≤200Ωm, signifies shaley to clayey lithology of the Patala Formation, indicating weathering and erosion by thermal fluid. The fourth layer corresponds to the migration of thermal plumes with a resistivity value of >25Ωm to ≤50Ωm, while a value of >05Ωm characterizes the fifth thermal spring layer of very low resistivity to ≤25Ωm. The very low resistivity values observed in the fifth layer are indicative of an anomalous zone, a characteristic feature of thermal springs. This low resistivity can be attributed to the high concentration of dissolved electrolytes within the mineral-rich thermal fluids. These fluids likely facilitate the alteration, weathering, and erosion of the surrounding rock formations, further enhancing the conductive nature of the zone. The Tattapani thermal spring exhibits a depth range of approximately 35-40 meters, increasing in the northeast-southwest (NE-SW) direction. Thermal plumes, primarily migrating in a NE-SW direction, have a depth range of about 25 meters. The VES data also delineates two aquifers: a shallow aquifer at approximately 10 meters’ depth and a deeper aquifer extending up to 20 meters, both hosted within the sandstone lithology. The shallow depth of the thermal plumes raises concerns about potential contamination of the deeper groundwater aquifer due to their overlapping depths. However, the presence of a barrier layer composed of shaley clay likely protects the shallow aquifer from current contamination. VES data revealed high-resistivity zones (dolomite) and low-resistivity zones (shale), consistent with Cambrian-Paleocene formations. The thermal spring is likely to emerge to the surface through a weak zone along the contact of shale and dolomite. A close correlation between the geological and resistivity sections suggests the presence of a fault or weak zone underlying the spring. This structure could facilitate a thermal convection cell, drive hot water upwelling, and potentially source it from the Poonch River. Detailed magnetic, gravity, and geochemical surveys are recommended to portray the deep-seated structure of the Tattapani thermal spring, while a geochemical survey will demarcate the contamination source by plume migration. Geothermometry and isotopic analysis are also recommended to show the subsurface temperature of thermal water.